Adolescencia, variación lingüística, competencia metacomunicativa y enseñanza de la lengua - Antonio Miguel Bañón Hernández (Estudios de Lingüística, 1993)
What we have aimed in the first part of the present paper is to carry out an analysis of some value judgement processes of linguistic variation from the evidence of two hundred and thirty-four Murcian adolescents registered in Compulsary Secondary Education Courses (ESO). Thus, we will both with the asumption of, adscription, adequacy, and adhesion to semio-linguistic habits —processes all related with maintenance attitudes—, and with the insiders' and outsiders' adversion to, accommodation to, and assimilation of semio-linguistic habits -processes all, on the other hand, following transformation attitudes. In the second part we will allude to some issues related with language teaching to nonstandard speakers or to non-standard-speaking communities.